2018
DOI: 10.1111/ecog.03889
|View full text |Cite
|
Sign up to set email alerts
|

Geographic variation of body size in New World anurans: energy and water in a balance

Abstract: The validity of Bergmann's rule, perhaps the best known ecogeographical rule, has been questioned for ectothermic species. Here, we explore the interspecific version of the rule documenting body size gradients for anurans across the whole New World and evaluating which environmental variables best explain the observed patterns. We assembled a dataset of body sizes for 2761 anuran species of the Western Hemisphere and conducted assemblage-based and cross-species analyses that consider the spatial and phylogenet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 88 publications
(218 reference statements)
3
43
0
Order By: Relevance
“…Macroecological studies on amphibians have revealed highly conflicting evidence for a role of temperature as an agent of spatial gradients in body size (Feder et al 1982, Ashton 2002, Olalla-Tarraga and Rodriguez 2007, Adams and Church 2008, Cvetkovic et al 2009, and the only known study on caecilians, on one species, showed a link with elevation (Measey and Van Dongen 2006). In contrast, the role of water-deprivation as a source of selection for larger body size as an adaptation to reduce rates of evapotranspiration has increasingly gained support (Olalla-Tarraga et al 2009, Gouveia and Correia 2016, Amado et al 2019. Our evidence, stemming from a complete coverage of caecilians, strongly supports the hypothesis that increases in body size are promoted by aridity -in particular among nonaquatic species, which reinforces the functional role of water conservation.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Macroecological studies on amphibians have revealed highly conflicting evidence for a role of temperature as an agent of spatial gradients in body size (Feder et al 1982, Ashton 2002, Olalla-Tarraga and Rodriguez 2007, Adams and Church 2008, Cvetkovic et al 2009, and the only known study on caecilians, on one species, showed a link with elevation (Measey and Van Dongen 2006). In contrast, the role of water-deprivation as a source of selection for larger body size as an adaptation to reduce rates of evapotranspiration has increasingly gained support (Olalla-Tarraga et al 2009, Gouveia and Correia 2016, Amado et al 2019. Our evidence, stemming from a complete coverage of caecilians, strongly supports the hypothesis that increases in body size are promoted by aridity -in particular among nonaquatic species, which reinforces the functional role of water conservation.…”
Section: Discussionsupporting
confidence: 70%
“…The leading rule, Bergmann's rule -increases in body sizes toward colder climates as greater body mass, relative to surface area, reduces heat loss (Bergmann 1847) -has set the theoretical benchmark for research on large-scale patterns of animal size (James 1970, Blackburn et al 1999, Meiri and Dayan 2003. However, evidence from across the animal kingdom reveals that Bergmann's rule tends to hold in endotherms (Freckleton et al 2003, Meiri and Dayan 2003, de Queiroz and Ashton 2004, Olson et al 2009, but see Riemer et al 2018), while its validity is inconsistent in ectotherms (Ashton and Feldman 2003, Olalla-Tarraga et al 2006, Olalla-Tarraga and Rodriguez 2007, Pincheira-Donoso et al 2007, Adams and Church 2008, Pincheira-Donoso and Meiri 2013, Feldman and Meiri 2014, Moreno-Azocar et al 2015, Amado et al 2019, Slavenko et al 2019). These discrepancies have discredited temperature as a primary driver of body size clines (Pincheira-Donoso 2010, Meiri 2011, Olalla-Tarraga 2011.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These differences between predictors highlight the discrepancy of constraints that differently affect organismal body length and body geometry. Previous works already stressed that geographical size variation in amphibian species may have multiple causes (Adams & Church, ; Amado et al., ; Gouveia & Correia, ; Olalla‐Tárraga & Rodríguez, ; Sinsch et al., ). More specifically, for E. calamita , geographical variation in size was suggested to be a result of the impact of temperature, type of microhabitat for hibernation and habitat constraints on growth rates.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the variation in SA:V has been recurrently suggested as the cause of body size responses to climatic gradients, most inferences on organismal size clines stem from single linear measurements of body length as a size metric instead of direct SA:V estimates (Amado, Bidau, & Olalla-Tárraga, 2018;Gouveia & Correia, 2016;Olalla-Tárraga & Rodríguez, 2007;Slavenko & Meiri, 2015). This can be mainly explained due to the inherent technical limitations in the capture of geometric measurements of animal's bodies.…”
Section: Introductionmentioning
confidence: 99%